Bears Ears National Monument and Outdoor Recreation in San Juan County, Utah. Issue 7 (3rd July 2021) - Smith, Jordan W.; Wilkins, Emily J.; Miller, Anna B.
Abstract: This policy analysis provides a focused look at the influence of the creation, and subsequent downsizing, of Bears Ears National Monument on outdoor recreation and industries related to outdoor recreation in San Juan County, Utah. Our findings suggest: (1) The creation of the monument has resulted in an increase in the amount of outdoor recreation occurring within the county; (2) Several outdoor recreation-related industries have grown since Bears Ears National Monument was created; and (3) The growth in outdoor recreation-related industries is not related to the increased concentration of outdoor recreation occurring within the county. Municipal and county leaders can take some solace from the finding that several of the county's outdoor recreation-related industries have grown. However, strategies that generate more revenue from the rising number of outdoor recreationists visiting the region can bring added economic benefits to local communities.